1959
DOI: 10.1103/physrev.114.502
|View full text |Cite
|
Sign up to set email alerts
|

Lifetime of the 186-kev Level of Thorium-231

Abstract: The lifetime of the 186-kev level of Th 231 has been studied following u 2 35 alpha decay. The half-life value of this level is 0.77 ± 0.12 ~sec.-3-

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

1961
1961
2013
2013

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(2 citation statements)
references
References 11 publications
0
2
0
Order By: Relevance
“…showed that the alanine of the peptide portion of the nucleotide, and of the cell wall, was composed of 1/3 L-isomer and 2/3 D-isomer. Strominger and Ito (1959) inferred that, since incomplete peptides were also induced, the peptide portion was synthesised by stepwise addition of amino-acids, and succeeded in separating each of the enzymes catalysing the stepwise addition of (1) Nathensen and Strominger (1959) showed that pencillin inhibited DAP incorporation and cell wall synthesis in E. coli in a manner analogous to the inhibition of lysine incorporation and cell wall synthesis in Staph. aureus.…”
Section: Cell Wall Structure and Penicillin Actionmentioning
confidence: 94%
See 1 more Smart Citation
“…showed that the alanine of the peptide portion of the nucleotide, and of the cell wall, was composed of 1/3 L-isomer and 2/3 D-isomer. Strominger and Ito (1959) inferred that, since incomplete peptides were also induced, the peptide portion was synthesised by stepwise addition of amino-acids, and succeeded in separating each of the enzymes catalysing the stepwise addition of (1) Nathensen and Strominger (1959) showed that pencillin inhibited DAP incorporation and cell wall synthesis in E. coli in a manner analogous to the inhibition of lysine incorporation and cell wall synthesis in Staph. aureus.…”
Section: Cell Wall Structure and Penicillin Actionmentioning
confidence: 94%
“…Cytidine nucleotides have also been found to accumulate in a strain of Staph. aureus inhibited by this substance (Armstrong, Baddiley, Buchanan and Carss, 1958 ;Strominger, 1959). found that a Dm-requiring mutant of E. coli contained a high steady state concentration of a uridine nucleotide in which the peptide portion was represented as L-alanine-D-glutamic acid-meso-DAP-D-alanine-D-alanine.…”
Section: Cell Wall Structure and Penicillin Actionmentioning
confidence: 96%